Factors for severe outcomes following SARS-CoV-2 infection in people with cystic fibrosis in Europe - Jung, Andreas; Orenti, Annalisa; Dunlevy, Fiona; Aleksejeva, Elina; Bakkeheim, Egil; Bobrovnichy, Vladimir; Carr, Siobhán B; Colombo, Carla; Corvol, Harriet; Cosgriff, Rebecca; Daneau, Géraldine; Dogru, Deniz; et al. (ERJ open research, 2021)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in people with cystic fibrosis (pwCF) can lead to severe outcomes. METHODS: In this observational study, the European Cystic Fibrosis Society Patient Registry collected data on pwCF and SARS-CoV-2 infection to estimate incidence, describe clinical presentation and investigate factors associated with severe outcomes using multivariable analysis. RESULTS: Up to December 31, 2020, 26 countries reported information on 828 pwCF and SARS-CoV-2 infection. Incidence was 17.2 per 1000 pwCF (95% CI: 16.0-18.4). Median age was 24 years, 48.4% were male and 9.4% had lung transplants. SARS-CoV-2 incidence was higher in lung-transplanted (28.6; 95% CI: 22.7-35.5) versus non-lung-transplanted pwCF (16.6; 95% CI: 15.4-17.8) (p≤0.001).SARS-CoV-2 infection caused symptomatic illness in 75.7%. Factors associated with symptomatic SARS-CoV-2 infection were age >40 years, at least one F508del mutation and pancreatic insufficiency.Overall, 23.7% of pwCF were admitted to hospital, 2.5% of those to intensive care, and regretfully 11 (1.4%) died. Hospitalisation, oxygen therapy, intensive care, respiratory support and death were 2- to 6-fold more frequent in lung-transplanted versus non-lung-transplanted pwCF.Factors associated with hospitalisation and oxygen therapy were lung transplantation, cystic fibrosis-related diabetes (CFRD), moderate or severe lung disease and azithromycin use (often considered a surrogate marker for Pseudomonas aeruginosa infection and poorer lung function). CONCLUSION: SARS-CoV-2 infection yielded high morbidity and hospitalisation in pwCF. PwCF with forced expiratory volume in 1 s <70% predicted, CFRD and those with lung transplants are at particular risk of more severe outcomes.